INSIDER TRADING DALAM PASAR MODAL TERDESENTRALISASI: DAMPAK HUKUM - Sonny Dwi Asmoro Putra; Vika Andarini (Fakultas Ilmu Sosial dan Humaniora, 2025)
This study examines insider trading within decentralized capital markets, focusing on its legal implications. The primary objective is to understand how insider trading affects market integrity, investor trust, and the broader regulatory environment in decentralized finance (DeFi). Using a qualitative approach, the research analyzes case studies of reported insider trading incidents in blockchain-based platforms and evaluates existing legal frameworks governing such activities. Data is collected through literature reviews, legal document analysis, and expert interviews. The findings reveal significant gaps in the regulatory oversight of insider trading in decentralized markets due to the pseudonymous nature of blockchain and the absence of centralized regulatory authorities. Furthermore, the study highlights that while blockchain technology offers transparency, it also poses challenges in identifying and prosecuting offenders. The research concludes that strengthening international cooperation and creating adaptive legal frameworks are essential to mitigate insider trading risks in decentralized markets. Such measures will enhance investor protection, foster trust, and promote fair market practices in the rapidly growing DeFi ecosystem.